Problems of false medicines' distribution and prospects of combat: survey of specialists and consumers results - Lebed, Serhii; Nemchenko, Alla (ScienceRise: Pharmaceutical Science, 2021)
The aim: comparative analysis of the results of a questionnaire survey of pharmaceutical and medical professionals and consumers, conducted by the authors during 2019-2021 to identify opinions on which there are coincidences and differences, as well as an assessment of the problem of drug counterfeiting in Ukraine to develop approaches to prevent their spread. Materials and methods. The study used scientific publications, as well as the results of a survey of specialists of the State Service of Ukraine for Medicines and Drug Control (State Medical Service) and its territorial bodies, pharmaceutical and medical professionals of health care institutions and consumers on the fight against drug falsification. The research was conducted using the methods of questionnaires, systematization and generalization. Results. According to the results of a comprehensive questionnaire during 2019-2021, it was found that the share of CM in the Ukrainian pharmaceutical market is estimated at 5 % by a majority of respondents on average 58.5 %, including 59.7 % of experts of the State Medical Service, 42.3 % of pharmacy specialists, 11.4 % by doctors and 73.5 % by consumers. Respondents' answers about the signs of drug falsification differ significantly, so most experts believe that this is a change in the usual signs (taste, smell, color), while pharmacy specialists - labelling in a foreign language, doctors - no therapeutic effect, for consumers it is a change in packaging design (labels) and a significantly lower price. The main sales channels of CM for experts and pharmacy specialists are e-commerce (68.7 % and 75.7 %, respectively), while the majority of consumers could not determine. Many experts and pharmacy specialists pointed to the need to introduce special security features of packaging in the form of 2d barcodes as the main method for protection and detection of CM (79.1 % and 39.6 %, respectively). Most of the surveyed pharmacy workers and consumers believe that the risk of purchasing counterfeit drugs is higher in the pharmacies of individual entrepreneurs or small pharmacy chains.The main problem that hinders the effective fight against drug counterfeiting was the imperfect legislation (68.7 %). Regarding effective tools in the fight against counterfeit drugs, experts called a significant strengthening of the powers of the regulatory body - following the example of the FDA (70.1 %). Conclusions. It is established that the most important priorities of the state policy for combating CM in Ukraine are the improvement of the system of state control and quality assurance of medicines, in particular 2d coding, as well as the need to strengthen the responsibility for drug falsification. The results of research on the problem of drug falsification indicate the feasibility of introducing a systematic survey for a wider range of respondents - professionals and consumers